2003
DOI: 10.1186/1471-2458-3-5
|View full text |Cite
|
Sign up to set email alerts
|

Airborne rhinovirus detection and effect of ultraviolet irradiation on detection by a semi-nested RT-PCR assay

Abstract: BackgroundRhinovirus, the most common cause of upper respiratory tract infections, has been implicated in asthma exacerbations and possibly asthma deaths. Although the method of transmission of rhinoviruses is disputed, several studies have demonstrated that aerosol transmission is a likely method of transmission among adults. As a first step in studies of possible airborne rhinovirus transmission, we developed methods to detect aerosolized rhinovirus by extending existing technology for detecting infectious a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 39 publications
(39 reference statements)
3
54
0
Order By: Relevance
“…For example, filters are attractive due to their high efficiency in trapping particles with an aerodynamic size of less than 500 nm (Verreault et al 2008). Additionally, filters can be used to collect air samples for at least 40 h (Myatt et al 2003), thus enhancing the probability of recovering low viral concentrations. However, it was previously reported that filters are less efficient for recovering infectious viral particles (Tseng and Li 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, filters are attractive due to their high efficiency in trapping particles with an aerodynamic size of less than 500 nm (Verreault et al 2008). Additionally, filters can be used to collect air samples for at least 40 h (Myatt et al 2003), thus enhancing the probability of recovering low viral concentrations. However, it was previously reported that filters are less efficient for recovering infectious viral particles (Tseng and Li 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, it was previously reported that filters are less efficient for recovering infectious viral particles (Tseng and Li 2005). Filter sampling coupled with PCR-based technology is considered a powerful method for detecting low concentrations of airborne viruses and is becoming highly recommended to evaluate bioaerosol contamination levels in different environments (Aintablian et al 1998;McCluskey et al 1996;Myatt et al 2003;Tsai et al 2006). Consequently, the development of sensitive techniques for airborne viral detection should be a priority.…”
Section: Introductionmentioning
confidence: 99%
“…Multiplex PCR uses several sets of primers to identify more than one organism within a sample. Reverse transcriptase PCR has been used to look for viruses (Myatt et al 2003). It uses the reverse transcriptase enzyme to copy RNA into a DNA template.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…PCR has also been successfully applied to air samples to detect and quantify bacteria, fungi, and viruses. (Agranovski et al 2004, Echavarria et al 2000, Myatt et al 2003, Nugent et al 1997, Schafer et al 2003, Williams et al 2001, Wu et al 2002. Commercial licenses are available for the DNA sequences for several fungal species commonly found in damp indoor environments (US EPA 2004).…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…These include the decontamination of air in hospital rooms (Banrud et al, 1999;Botzenhart et al, 1976;Rudnick, 2001), the disinfecting of biological safety cabinet interior surfaces (Fleming et al, 1995), and the sterilization of consumable products (Varnam, 1991). Microbial agent-specific studies using UVGI for decontamination have been reported for rhinovirus (Myatt et al, 2003), Mycobacterium tuberculosis (Ko et al, 2002;Nicas et. al., 1999;Riley et al, 1976), and Serratia marcescens (Ko et al, 2002).…”
Section: Introductionmentioning
confidence: 99%